The Power of Politeness Strategies in EFL Student-Teacher Interaction: Teacher’s Gender Perspective - Riyan Febriansyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
The nature of student-teacher interaction is often influenced by the teachers’ actions and utterances. In fact, student-teacher interaction could be felt like either threatening or enjoyable. Teachers’ politeness will result in enjoyable student-teacher interaction. Very few studies about politeness on the teachers’ gender perspectives have been conducted. Therefore, this study is aimed to investigate the kinds of politeness strategies used by male and female teachers in powering EFL classroom, and to elaborate how the power of politeness strategies run the EFL student-teacher interaction. The participants are several teachers and students who conduct the English Intensive Course Program in an undergraduate university. Many students-teacher interactions using English are found in those course program, since the courses require the classroom participants to communicate in English. This research followed qualitative research design and used observation to collect data. Applying Brown and Levinson’s theory of politeness, the results show that politeness strategies bring a lively and friendly atmosphere during the classroom interaction. Specifically for female teachers who mostly use positive politeness strategy, they build more interaction with the student rather male teachers. Positive politeness strategy focused on the students’ positive face by expressing the number of utterances that want to be listened to by the students. It keeps students to have willingness to communicate so that the student-teacher interaction in EFL classroom can be maximized.